Measuring child survival for the Millennium Development Goals in Africa: what have we learned and what more is needed to evaluate the Sustainable Development Goals?. Issue 1 (31st December 2020) - Brault, Marie A.; Mwinga, Kasonde; Kipp, Aaron M.; Kennedy, Stephen B.; Maimbolwa, Margaret; Moyo, Precious; Ngure, Kenneth; Haley, Connie A.; Vermund, Sten H.
ABSTRACT: Reducing child mortality is a key global health challenge. We examined reasons for greater or lesser success in meeting under-five mortality rate reductions, i.e. Millennium Development Goal #4, between 1990 and 2015 in Sub-Saharan Africa where child mortality remains high. We first examined factors associated with child mortality from all World Health Organization African Region nations during the Millennium Development Goal period. This analysis was followed by case studies of the facilitators and barriers to Millennium Development Goal #4 in four countries – Kenya, Liberia, Zambia, and Zimbabwe. Quantitative indicators, policy documents, and qualitative interviews and focus groups were collected from each country to examine factors within and across countries related to child mortality. We found familiar themes that highlighted the need for both specific services (e.g. primary care access, emergency obstetric and neonatal care) and general management (e.g. strong health governance and leadership, increasing community health workers, quality of care). We also identified methodological opportunities and challenges to assessing progress in child health, which can provide insights to similar efforts during the Sustainable Development Goal period. Specifically, it is important for countries to adapt general international goals and measurements to their national context, considering baseline mortality rates and health information systems, to develop country-specific goals. It will also be critical to develop more rigorous measurement tools and indicators to accurately characterize maternal, neonatal, and child health systems, particularly in the area of governance and leadership. Valuable lessons can be learned from Millennium Development Goal successes and failures, as well as how they are evaluated. As countries seek to lower child mortality further during the Sustainable Development Goal period, it will be necessary to prioritize and support countries in quantitative and qualitative data collection to assess and contextualize progress, identifying areas needing improvement.